1996
DOI: 10.1016/s0022-5347(01)66356-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Fibrous Histiocytoma of the Spermatic Cord

Abstract: Malignant fibrous histiocytoma presents earlier in the spermatic cord than at other sites and seems to have a more favorable prognosis. Ultrasound may aid in the diagnosis. Definitive treatment is radical orchiectomy but localized radiotherapy may decrease local recurrence rates. Satellite lesions at surgery indicate a poorer prognosis. Metastases may develop late in the lungs or mesentery, and so long-term followup is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In spermatic cord sarcomas, there is a high rate of local recurrence after treatment with surgery alone (71% of cases), and some authors recommend postoperative radiation therapy to reduce the recurrence rate. The growth of paratesticular malignant fibrous histiocytoma is more obvious than growth at other sites, so that patients present earlier and have a slightly more favorable prognosis (18).…”
Section: Malignant Fibrous Histiocytomamentioning
confidence: 99%
“…In spermatic cord sarcomas, there is a high rate of local recurrence after treatment with surgery alone (71% of cases), and some authors recommend postoperative radiation therapy to reduce the recurrence rate. The growth of paratesticular malignant fibrous histiocytoma is more obvious than growth at other sites, so that patients present earlier and have a slightly more favorable prognosis (18).…”
Section: Malignant Fibrous Histiocytomamentioning
confidence: 99%
“…Twenty‐one cases of MFH of the spermatic cord have been reported in the Japanese literature, 1,2 and there have been only 22 other cases in the worldwide literature. 3–6 …”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐one cases of MFH of the spermatic cord have been reported in the Japanese literature and there have been only 22 other cases in the worldwide literature. 1–6 The relative rarity of this tumor makes its treatment and prognosis controversial. We report one additional case of MFH of the spermatic cord.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, almost 80% of spermatic cord malignant fibrous histiocytoma occurred in patients who were ≥ 50 years old (Table 1). Spermatic cord malignant fibrous histiocytoma generally presented as a slowly growing, 4,5,12 Several patients felt mild pain in the tumour region. The largest spermatic cord malignant fibrous histiocytoma recorded in the literature was a well-encapsulated mass, measuring 27 × 22 × 17 cm.…”
Section: Lw Xu Yl Yu G-h LI Spermatic Cord Malignant Fibrous Histiomentioning
confidence: 99%
“…2 Some pathologists consider malignant fibrous histiocytoma to be a discrete entity that may be subclassified into specific sarcoma types. 3 Malignant fibrous histiocytoma arises mainly in the deep soft tissues of the extremities (70%) and retroperitoneum (16%) and, occasionally, in the inguinal region; 4 it rarely involves the spermatic cord, and was first described at this site by Cole et al in 1972. 5 A literature search revealed that 33 cases of spermatic cord malignant fibrous histiocytoma have been reported in English-language journals.…”
Section: Introductionmentioning
confidence: 99%